2017
DOI: 10.1177/1098612x16688806
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical bacteriuria in cats: prevalence, findings on contemporaneous urinalyses and clinical risk factors

Abstract: Objectives Subclinical bacteriuria (SB) is bacterial colonization of the urinary tract in the absence of clinical signs. The purposes of this study were to determine the prevalence of SB in cats and to describe results of the contemporaneous urinalysis. Secondarily, patient characteristics associated with SB were compared with those for cats without SB. Methods An electronic search identified all urine cultures performed on cats at a teaching hospital between 2009 and 2015. Results were subcategorized based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
55
2
6

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(84 citation statements)
references
References 25 publications
17
55
2
6
Order By: Relevance
“…We found females to be at higher risk for developing subclinical bacteriuria than males (OR, 6.9; Table 5), regardless of thyroid status, a finding that is in accord with other studies in cats 26,36 . However, we found that neither age nor age stage posed an increased risk for subclinical bacteriuria, similar to a large study of 179 middle‐aged to elderly cats, 27 but in contrast to others in which older age was a risk factor 26,36 . A possible explanation for these differences could be the selection of middle‐aged to older cats in our study (no cats <7 years of age were included), which likely affected the association between increasing age and subclinical bacteriuria.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found females to be at higher risk for developing subclinical bacteriuria than males (OR, 6.9; Table 5), regardless of thyroid status, a finding that is in accord with other studies in cats 26,36 . However, we found that neither age nor age stage posed an increased risk for subclinical bacteriuria, similar to a large study of 179 middle‐aged to elderly cats, 27 but in contrast to others in which older age was a risk factor 26,36 . A possible explanation for these differences could be the selection of middle‐aged to older cats in our study (no cats <7 years of age were included), which likely affected the association between increasing age and subclinical bacteriuria.…”
Section: Discussionsupporting
confidence: 90%
“…Although azotemia was not predictive of subclinical bacteriuria, evidence of kidney disease in the form of dilute urine specific gravity (<1.035) did increase the risk, similar to findings in some, 5,26,37 but not all studies 6,11,36 . In addition, both pyuria and bacteriuria were predictors for subclinical bacteriuria, similar to findings in other studies 6,11,26 . Although hematuria was common, it was not a predictor for subclinical bacteriuria in our study.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations